1957
DOI: 10.1677/joe.0.0160115
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Hormone on the Yield and Composition of Cows' Milk

Abstract: SUMMARY Using a single injection technique, a study has been made of the effect of growth hormone (GH) on the yield and composition of cows' milk. Six lactating cows comprising three sets of identical twins each received six different injection levels during a 78-day period. Quantities of GH injected ranged from 6·25 to 200 mg in geometric progression, and responses were measured for milk yield (lb.), fat percentage, and solids-not-fat percentage, together with the derivatives of these three. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…There were no other results which allowed us to draw a conclusion about the primary site of action of the hormone. A similar effect of growth hormone in raising the efficiency of milk synthesis was observed by Hutton (1957) If, as seems likely, GH stimulates an increase in the amount of energy used for milk synthesis, without an increase in basal metabolic rate as is the case with exogenous thyroxine (Blaxter, 1952), consideration must be given to the possibility of raising GH level in the blood of cows as a means of increasing the efficiency of food utilization for milk synthesis. There are three ways of increasing blood GH level: environmental, pharmacological and nutritional; some of these have been examined at Shinfield.…”
Section: Vol 37mentioning
confidence: 74%
“…There were no other results which allowed us to draw a conclusion about the primary site of action of the hormone. A similar effect of growth hormone in raising the efficiency of milk synthesis was observed by Hutton (1957) If, as seems likely, GH stimulates an increase in the amount of energy used for milk synthesis, without an increase in basal metabolic rate as is the case with exogenous thyroxine (Blaxter, 1952), consideration must be given to the possibility of raising GH level in the blood of cows as a means of increasing the efficiency of food utilization for milk synthesis. There are three ways of increasing blood GH level: environmental, pharmacological and nutritional; some of these have been examined at Shinfield.…”
Section: Vol 37mentioning
confidence: 74%
“…Even so, enough GH could be purified to support limited basic, short-term research using exogenous bovine GH (Brumby and Hancock 1955;Cotes et aL. 1949|' Johnsson andHart 1986;Hutton 1957;Machlin 1973). …”
Section: Production Performance Of Dairy Cows Treated With Growth mentioning
confidence: 99%
“…INTRODUCTION synthesis using bacterial recombinants has IT HAS BEEN KNOWN for several decades that introduced the theoretical prospect of subcutaneous injection of bovine growth unlimited supplies of the hormone (Miozzari, hormone (bGH), of varying purity, will 1981) and it has recently been shown that increase milk production in cows, particularly recombinantly-derived bGH stimulates milk after peak lactation (see Hutton, 1957 and production and improves food efficiency in Machlin, 1973 for references) but the cost of cattle (Bauman, DeGeeter, Peel, Lanza, extracting the hormone from pituitary glands Gorewit and Hammond, 1982a). Thus it was has always precluded the application of this considered important to investigate some of knowledge to practical dairy farming.…”
mentioning
confidence: 99%
“…The minimum quantity of hormone to stimulate yield has been examined in only one experiment which was based upon the 4-day milk yield response of six cows to one injection of several different doses of the hormone (Hutton, 1957). However, these results are not reliable since more recent work showed that the milk yield response to bGH takes up to seven daily injections to develop completely (Bullis, Bush and Bartos, 1965;Machlin, 1973).…”
mentioning
confidence: 99%